A Development of Ladies Jeans Enterprise Management System: Pembangunan Sistem Pengurusan Ladies Jeans Enterprise - Darmaji, Rikey Kurniawan; Selamat, Norhanim; Yusliza Hassim (Applied Information Technology And Computer Science, 2024)
Effective business management is crucial for ensuring business growth and preventing losses. However, Ladies Jeans Enterprise has experienced losses due to their reliance on manual processes, which result in wasted time and energy in today’s fast-paced world. Furthermore, these manual procedures have led to a weak inventory management system, worsening the challenges they face. To optimise their business operations and overcome these issues, the Ladies Jeans Enterprise Management System was developed. Built using web technology and a multi-tier architecture, this system incorporates a prototype methodology in its development. The barcode technology and inventory control method implemented in the system also facilitate efficient inventory management system for the enterprise. The aim is to provide a centralised platform that facilitates management work at Ladies Jeans Enterprise, improving efficiency and promoting growth. With its implementation, the system is expected to enhance their overall business management practices and drive success.